Improvement of the watermelon growing system in the irrigated areas - Araújo, José P. de; Freire, Luiz C.; Faria, Clementino M. B. de (Pesquisa Agropecuaria Brasileira, 2014)
Watermelon variety Charleston Gray (Citrullus vulgaris Schrad) has performed very well in the "Submédio São Francisco River" region in Northeastern Brazil. However, blossom-end rot has been a restraint to the development of the crop in this region, causing up to 40% yield reduction, Agricultural Research Center for the Semi-Arid Tropic of Brazil (CPATSA)/Brazilian Agricultural Research Corporation (EMBRAPA) has been working in a project to solve this problem. This paper presents the results of a study conducted with two treatments: modified and traditional cropping systems. The former, using the new technology developed by research studies, and, the latter, using growers’ currently employed technology. The main result of this study concerns the reduction of of rate of fruits presenting blossom-end rot. The use of calcium fertilizer (CaO and MgO) lowered the number of diseased fruits from 677 per hectare, in the traditional cropping system, to 45 per hectare, in the modified cropping system. Also, the rational fertilization and pest and disease control permitted a Cr 33,679.00 - per hectare-reduction in production costs (43,3% reduction in costs). The reduction in production costs and the increase in productivity resulted in an increase in net return from Cr 63,651.00, in the traditional cropping system, to Cr 175,207,00, in the modified cropping system.